Comparison Effectiveness Of Ice Pack Therapy And Cinnamin Decil On Reduce Perineal Wound Pain In Padasuka Village Working Area, Kab. Lebak The Year 2022 - Yuni Nuraeni Astuti (Pusat Riset dan Inovasi Nasional, 2023)
Background : WHO (2018) states that the Maternal Mortality Rate (MMR), there are approximately 830 women who die every day due to things that can actually be anticipated which are generally related to the process of pregnancy and childbirth. Pain or morbidity that occurs early in the puerperium is generally caused by the influence of mastitis, urinary tract infections, infections of episiotomy and laceration wounds, and other diseases. The puerperium is the period since the birth of the baby, the discharge of the amniotic fluid, the birth of the placenta, and the membranes needed to restore the health condition of the uterine organs back to their pre-pregnancy state.. This period generally occurs around 6 weeks. The general condition in postpartum mothers is feeling of pain and discomfort in the area of ​​ruptured sutures (perineal wounds).Purpose : Knowing the Comparative Effectiveness of Ice Pack Therapy and Cinnamon Decoction on Reducing Perineal Wound Pain in Padauka Village in 2022Method : The method in this research is experiment. The type of research used is Quasi Experimental. The population in this study were all postpartum mothers in the working area of ​​Padasuka Village, Kab. Lebak as many as 87 samples. The sample in this study was 30 postpartum mothers. The sampling technique is Purposive Sampling.Result : There is a comparative effect of ice pack and cinnamon extract therapy on reducing the intensity of perineal wound pain level II, this is in line with the results of the Mann Whitney U test with a significant value of 0.000 <0.05.Conclusion and Suggestion : There is a comparison of the effect of ice pack therapy and cinnamon extract on reducing pain intensity in grade II penrineal wounds. Treatment of perineal tear pain during the postpartum period is an important thing that is needed by postpartum mothers, therefore it is very necessary to have a good treatment and intensive care that is able to overcome the mother's complaints of felt wound pain so that the mother feels comfortable during her postpartum period.